1999
DOI: 10.1046/j.1365-2133.1999.03043.x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for a role of human herpesvirus type 8 in sarcoidosis: molecular and serological analysis

Abstract: The aim of this study was to analyse the association between human herpesvirus type 8 (HHV8) and sarcoidosis. Using nested polymerase chain reaction (PCR), we tested the presence of HHV8 DNA sequences in 13 skin specimens and peripheral blood mononuclear cells from eight patients suffering from sarcoidosis. We also looked for the presence of HHV8 antibodies in the sera of 28 patients with sarcoidosis using three techniques: two indirect immunofluorescence assays and an enzyme-linked immunosorbent assay with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…HLA Class II antigens encoded by HLA-DRB1 and HLA-DQB1 alleles are also consistently associated with AfricanAmericans and Caucasians who develop Löfgren's syndrome, an acute form of sarcoidosis characterised by bilateral hilar lymphadenopathy, polyarthralgia and erythema nodosum and which has a good prognosis (Lebbe et al 1999;Baughman et al 2003;Iannuzzi et al 2003;McGuire-Gray et al 2006; Thomas and Hunninghake 2006). HLA-DQB1*0201 and HLA-DRB1*0301 are also associated with Löfgren's syndrome together with reduced T H 1 responses and cytokine expression (Idali et al 2006), with these patients showing good prognosis (Wahlström et al , 2009Grunewald et al 2010).…”
Section: Genetic Featuresmentioning
confidence: 92%
See 1 more Smart Citation
“…HLA Class II antigens encoded by HLA-DRB1 and HLA-DQB1 alleles are also consistently associated with AfricanAmericans and Caucasians who develop Löfgren's syndrome, an acute form of sarcoidosis characterised by bilateral hilar lymphadenopathy, polyarthralgia and erythema nodosum and which has a good prognosis (Lebbe et al 1999;Baughman et al 2003;Iannuzzi et al 2003;McGuire-Gray et al 2006; Thomas and Hunninghake 2006). HLA-DQB1*0201 and HLA-DRB1*0301 are also associated with Löfgren's syndrome together with reduced T H 1 responses and cytokine expression (Idali et al 2006), with these patients showing good prognosis (Wahlström et al , 2009Grunewald et al 2010).…”
Section: Genetic Featuresmentioning
confidence: 92%
“…Similarly, evidence linking Rickettsia helvetica, Chlamydia pneumonia and Tropheryma whipplei to sarcoidosis is weak, based on case reports (Chen and Moller 2008) and studies did not detect Borrelia burgdorferi DNA in sarcoid tissues by PCR analysis (Thomas and Hunninghake 2006) Epstein-Barr virus, human herpesvirus-8, Coxsackie virus, mycobacteriophage, herpes simplex have been suggested as possible aetiological agents, but most recent findings indicate otherwise (Lebbe et al 1999;Gazouli et al 2002;Thomas and Hunninghake 2006) Sarcoidosis development is documented in patients receiving interferon-a therapy, a stimulator of T cell activity, particularly with high incidence in a subgroup of patients with sarcoidosis who have chronic hepatitis C infection. High incidences of sarcoidosis in untreated hepatitis C also suggest an association (Bolukbas et al 2005;Celik et al 2005).…”
Section: Immunopathogenesis Of Sarcoidosismentioning
confidence: 94%
“…Controversial results still remain concerning the presence of mycobacterial DNA in sarcoid lesions [16]. Retroviruses [17]and HHV-8 [18]have also been searched for in sarcoidosis tissues. Recently, Ishige et al [19]detected Propionibacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Borrelia burgdorferi was proposed as a possible agent of sarcoidosis by a Chinese group [16] on the basis of the elevated titers of serum antibodies in sarcoid patients, but the same group later concluded that the elevation is a nonspecific response [42]. Human herpesvirus 8 was proposed by an English group [5] to be a cause of sarcoidosis on the basis of the results of nested PCR, but later research on these lines by other groups [6,23,25] gave negative results.…”
Section: Putative Causative Agents Of Sarcoidosismentioning
confidence: 99%